Assessment of the Current Situation and Solutions to Attract Australian FDI Capital to Vietnam in the Context of International Integration (International Journal of Scientific Research and Management (IJSRM), 2024)
Foreign Direct Investment (FDI) has played a pivotal role in Vietnam’s economic transformation, significantly contributing to industrialization, job creation, and export growth. Since the introduction of the Law on Foreign Investment in 1987 and Vietnam’s accession to the World Trade Organization (WTO) in 2007, the country has emerged as a leading destination for foreign investors in Southeast Asia. Key sectors attracting FDI include manufacturing, real estate, and services, which have driven economic development and facilitated Vietnam’s integration into the global economy. Despite these successes, challenges remain that hinder FDI’s full potential, including administrative inefficiencies, complex regulations, corruption, and inadequate infrastructure. The shortage of highly skilled labor, especially in technology-driven fields, also limits the country’s ability to attract higher-value FDI projects. Moreover, there are regional disparities in FDI distribution, with major urban centers like Ho Chi Minh City and Hanoi receiving most investments, while rural areas are often overlooked. The impact of new-generation Free Trade Agreements (FTAs), such as the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP) and the Regional Comprehensive Economic Partnership (RCEP), is also examined. These agreements enhance market access, legal protections for investors, and reduce trade barriers, making Vietnam increasingly attractive for high-tech and service industries. This paper assesses the current FDI landscape in Vietnam, identifying opportunities and challenges for foreign investors. Recommendations include simplifying business procedures, implementing anti-corruption measures, improving infrastructure, and enhancing workforce training to address skills gaps. By adopting these reforms, Vietnam can attract higher-quality investments, strengthen ties with global supply chains, and foster sustainable economic growth. Additionally, the research emphasizes the importance of building stronger partnerships between FDI enterprises and local firms to ensure the widespread distribution of investment benefits across the economy. With a more favorable investment climate, Vietnam can reinforce its position as a premier destination for global investors and enhance its role in the international market.